Novel polyamine-based Histone deacetylases-Lysine demethylase 1 dual binding inhibitors. Issue 6 (1st April 2018) - Milelli, Andrea; Marchetti, Chiara; Turrini, Eleonora; Catanzaro, Elena; Mazzone, Roberta; Tomaselli, Daniela; Fimognari, Carmela; Tumiatti, Vincenzo; Minarini, Anna
Graphical abstract: Abstract: Epigenetic modulators Histone deacetylases (HDACs) and Lysine demethylase (LSD1) are validated targets for anticancer therapy. Both HDAC1/2 and LSD1 are found in association with the repressor protein CoREST in a transcriptional co-repressor complex, which is responsible for gene silencing. Combined modulation of both targets results in a synergistic antiproliferative activity. In the present investigation, we report about the design and synthesis of a series of polyamine-based HDACs-LSD1 dual binding inhibitors obtained by coupling Vorinostat and Tranylcypromine. Compound4 emerged as the most promising of the synthesized series, showing good inhibitory activity towards HDAC1 and LSD1 either in vitro and in cell-based assay (Ki = 42.52 ± 8.94 nM and IC50  = 3.85 μM, respectively). Furthermore, at 70.0 µM compound4 induced a more pronounced cytotoxic effect than Vorinostat (68.6% vs 56.6% of dead cells) in MCF7 cancer cell line.